(untitled) (LACCEI, 2024)
Knowledge management as a line of research within the framework of management sciences has become an area of ​​transversal interest for organizations, especially those that base their strategy on research, development and innovation (R+D+i) activities. ). This research includes a conceptual approach to the design of a model for measuring the maturity of knowledge management in R+D+i centers in Latin America. The methodological design implemented is of an exploratory type, of a non-experimental design and based on mixed methods based on the use of systematic literature review methodologies and tools, and qualitative content analysis and scientometrics. The final result is a first version of the maturity model as a measurement tool for research and development centers, which makes it possible to identify the current stage of the organization or its knowledge structures and to generate guiding elements to move to a new stage